Male Infertility Diagnosis: Improvement of Genetic Analysis Performance by the Introduction of Pre-Diagnostic Genes in a Next-Generation Sequencing Custom-Made Panel - Precone, Vincenza; Cannarella, Rossella; Paolacci, Stefano; Busetto, Gian Maria; Beccari, Tommaso; Stuppia, Liborio; Tonini, Gerolamo; Zulian, Alessandra; Marceddu, Giuseppe; Calogero, Aldo E.; Bertelli, Matteo (Frontiers in Endocrinology, 2021)
Background: Infertility affects about 7% of the general male population. The underlying cause of male infertility is undefined in about 50% of cases (idiopathic infertility). The number of genes involved in human spermatogenesis is over two thousand. Therefore, it is essential to analyze a large number of genes that may be involved in male infertility. This study aimed to test idiopathic male infertile patients negative for a validated panel of “diagnostic” genes, for a wide panel of genes that we have defined as “pre-diagnostic”. Methods: We developed a next-generation sequencing (NGS) gene panel including 65 pre-diagnostic genes that were used in 12 patients who were negative to a diagnostic genetic test for male infertility disorders, including primary spermatogenic failure and central hypogonadism, consisting of 110 genes. Results: After NGS sequencing, variants in pre-diagnostic genes were identified in 10/12 patients who were negative to a diagnostic test for primary spermatogenic failure (n=9) or central hypogonadism (n=1) due to mutations of single genes. Two pathogenic variants of DNAH5 and CFTR genes and 3 uncertain significance variants of DNAI1, DNAH11, and CCDC40 genes were found. Moreover, 3 variants with high impact were found in AMELY, CATSPER 2, and ADCY10 genes. Conclusion: This study suggests that searching for pre-diagnostic genes may be of relevance to find the cause of infertility in patients with apparently idiopathic primary spermatogenic failure due to mutations of single genes and central hypogonadism.